2013
DOI: 10.3767/003158513x669698
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of chrysosporia infecting reptiles: proposal of the new family <I>Nannizziopsiaceae</I> and five new species

Abstract: We have performed a phenotypic and phylogenetic study of a set of fungi, mostly of veterinary origin, morphologically similar to the Chrysosporium asexual morph of Nannizziopsis vriesii (Onygenales, Eurotiomycetidae, Eurotiomycetes, Ascomycota). The analysis of sequences of the D1-D2 domains of the 28S rDNA, including representatives of the different families of the Onygenales, revealed that N. vriesii and relatives form a distinct lineage within that order, which is proposed as the new family Nannizziopsiacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 49 publications
(70 reference statements)
2
107
1
Order By: Relevance
“…Numerous studies worldwide have demonstrated that ITS-5.8S rDNA can successfully distinguish most fungal species, an important characteristic for fungal identification and recognition (Schoch et al 2012, Kiss et al 2012. Although ITS-5.8S, β-tubulin, and the D1/ D2 region of the nuclear 28S subunit (nucLSU) sequences have all been used for phylogenetic reconstruction in the genus Chrysosporium, ITS-5.8S rDNA sequences alone were able to successfully distinguish Chrysosporium species in two studies (Stchigel et al 2013, Vidal et al 2000. Subsequent phylogenetic analyses in the genus Chrysosporium have been predominantly based on ITS-5.8S sequences , Vidal et al 2000, Pitt et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies worldwide have demonstrated that ITS-5.8S rDNA can successfully distinguish most fungal species, an important characteristic for fungal identification and recognition (Schoch et al 2012, Kiss et al 2012. Although ITS-5.8S, β-tubulin, and the D1/ D2 region of the nuclear 28S subunit (nucLSU) sequences have all been used for phylogenetic reconstruction in the genus Chrysosporium, ITS-5.8S rDNA sequences alone were able to successfully distinguish Chrysosporium species in two studies (Stchigel et al 2013, Vidal et al 2000. Subsequent phylogenetic analyses in the genus Chrysosporium have been predominantly based on ITS-5.8S sequences , Vidal et al 2000, Pitt et al 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Only six new species have been reported in the past 5 years, namely, C. guarroi J. Cabañes & Abarca (Abarca et al 2010), C. speluncarum A. Nováková & M. Kolařík (Nováková & Kolařík 2010), C. longisporum Stchigel, Deanna A. Sutton, Cano & Guarro (Stchigel et al 2013), C. magnasporum Stchigel, Cano, Mac Cormack & Guarro (Crous et al 2013), C. qinghaiense Y.F. Han, J.D.…”
Section: Introductionmentioning
confidence: 99%
“…The new genus Ophidiomyces was published recently to accommodate C. ophiodiicola, and we provide here an expanded description to facilitate the recognition of this emerging snake pathogen (29). While the present paper was under review, Stchigel et al (30) published a study that analyzed 19 isolates from reptile and human sources. The four Nannizziopsis species described in that study, including Nannizziopsis chlamydospora, Nannizziopsis draconii, Nannizziopsis arthrosporioides, and Nannizziopsis pluriseptata, differ from those described here based on a comparison of ITS sequence similarity, their analyses, and phenotypic features.…”
mentioning
confidence: 99%